Repetitive Transcranial Magnetic Stimulation for the Treatment of Complex Regional Pain Syndrome: A Pilot Study - Foglia SD; Drapeau CC; Ramdeo KR; Adams FC; Soppitt DB; Rehsi RS; Shanthanna H; Nelson AJ (Journal of Pain Research)
Stevie D Foglia,1 Chloe C Drapeau,2 Karishma R Ramdeo,2 Faith C Adams,2 Daniel B Soppitt,2 Ravjot S Rehsi,2 Harsha Shanthanna,1,3 Aimee J Nelson1,2 1School of Biomedical Engineering, McMaster University, Hamilton, ON, Canada; 2Department of Kinesiology, McMaster University, Hamilton, ON, Canada; 3Department of Anesthesia, McMaster University, Hamilton, ON, CanadaCorrespondence: Aimee J Nelson, Department of Kinesiology, McMaster University, 1280 Main Street West, Hamilton, ON, L8S 4K1, Canada, Tel +1 905-525-9140 x28053, Fax +1 905-523-6011, Email nelsonaj@mcmaster.caPurpose: Complex regional pain syndrome (CRPS) is a debilitating chronic pain condition characterized by sensory, motor, and autonomic dysfunction with a world-wide prevalence of 26.2 per 100,000 people per year and is 3 to 4 times more prevalent in females. Repetitive transcranial magnetic stimulation (rTMS) has shown to be beneficial for pain relief in neuropathic pain and initial evidence in CRPS is promising, but studies are limited. The objective of this study was to investigate the feasibility of using rTMS in CRPS patients, to improve pain intensity and quality of life.Patients and Methods: Six participants (5 lower limb, 1 upper limb, 42 ± 9 yr) took part in an open-label rTMS study comprised of a 9-week intervention and 6-month follow-up. Participants took part in a 4-week induction period (5 days per week) followed by a 5-week tapering period whereby the frequency of rTMS sessions per week was reduced. rTMS was delivered at 10 hz for 2000 pulses at 80% of resting motor threshold over the primary motor cortex. Feasibility was assessed as compliance of attending treatment sessions. Clinical outcomes included pain intensity using the numerical ratings scale, Pain Catastrophizing scale-EN-SF, PROMIS-29 v2.0 profile, and Rainbow Pain Scale.Results: All participants tolerated the study procedures and 83% of participants completed the 9-week intervention, deeming the protocol feasible. At six months follow-up, data was obtained from 3 individuals. Exploratory analysis revealed a significant reduction in pain intensity (~20%) immediately following the intervention. Categorical improvements in allodynia were observed in four patients immediately following the intervention.Conclusion: This study demonstrates that rTMS delivered over 9 weeks is feasible and well tolerated in individuals living with CRPS. However, there are challenges in collecting follow-up data for six months and appropriate measures must be taken in randomized controlled trials to ensure follow-up retention.Keywords: complex regional pain syndrome, repetitive transcranial magnetic stimulation, neuromodulation, chronic pain, feasibility